Effect of Hard Particles on Wear Resistance of Cold-Sprayed 2024 Aluminum Alloy Coatings - DAI Xueting, SONG Shengqiang, NAN Jian (Cailiao Baohu)
To address the issues of poor wear resistance and susceptibility to damage in pure 2024 aluminum alloy， four different hard particles， SiC， Al2O3， TiC and WC were mechanically mixed with 2024 aluminum alloy powder at a fixed ratio (5:2， volume ratio) and the mixture was uniformly blended.Cold spraying was used to prepare the coatings.The influence of the hard particles on the wear resistance of cold-sprayed 2024 aluminum alloy coatings was investigated using methods such as scanning electron microscopy (SEM)， microhardness testing， bonding strength testing， and friction-wear tests.Results showed that compared to the pure 2024 aluminum alloy coating， the hardness and bonding strength of the coatings increased as the density of the hard particles increased.The hardness of the 2024Al＋WC coating increased by 62.7%， reaching 247.8 HV0.05， and its bonding strength increased by 71.1%， reaching 60.4 MPa.Friction-wear test results indicated that although the addition of hard particles effectively improved the wear resistance of 2024 aluminum alloy coatings and significantly reduced weight loss due to wear， the larger density of TiC and WC particles caused the abrasive particles to adhere to the coating surface without falling off quickly， exacerbating wear on the 2024Al＋TiC and 2024Al＋WC coatings.The 2024Al＋Al2 O3 coating exhibited the lowest wear weight loss under different loads.Under 20 N and 30 N loads，the wear weight loss of the 2024Al＋Al2O3 coating reached 1.9 mg and 2.4 mg，respectively，a reduction of 77.9%and 81.1%compared to the 2024 aluminum alloy coating， demonstrating the best wear resistance.